Design and Analysis of Micro-Strip Yagi Shaped Antenna for Wi-Fi Application - Shahidi, Mohamad Izzat Asyraf (2017)
Due to increase in demand for wireless communication, cloud computing, as well as the development of IOT (Internet of Things) micro-strip antenna has become a choice as it offers compactness, small sized, and efficient performance. This paper explains a finding on the best optimized design for micro-strip Yagi shaped antenna by varying the width, length and spacing between reflector driven element and director. The design of micro-strip patch is created and simulated using the Computer Simulation Tool (CST) software for better gain and return loss and other parameters such as directivity, radiation pattern and power radiated. To verify the simulation result, a parametric studies are performed by testing the fabricated antenna. The aim of the Micro-strip Yagi shaped antenna is to achieve the mentioned goal for Wi-Fi application with the most compact design and operating frequency range at 5.2 GHz to 5.8 GHz.